Influence of Mechanical surface treatment on the strength of mixed adhesive joint. (2018) - Hirulkar, N.S.; Jaiswal, P.R.; Alessandro, Pirondi; Reis, Paulo
Abstract: Adhesive bonding is a promising joining technique in modern transport industries which provides for lightweight connection of dissimilar materials. However, available adhesive types have reached their limits in terms of durability and strength. A potential solution to this problem is the utilization of mixed adhesives. However, the influence of the surface preparation method on the performance of mixed adhesive joints has not been investigated thoroughly yet. The objective of this study is therefore to analyze such influence on the strength of mixed adhesive single lap joints. In this regard, five mechanical surface treatment methods were examined on aluminium alloy AA6082 using combinations of three different types of adhesives by means of static tensile tests. The results show significant increase in joint strength and ductility for DP 8005-AV138 compared to AV138 alone for sanding surface preparation. The roughness value in the range of Ra=1.7 to 3.1µm and Rm=36.5 to 44.60µm provide the highest shear strength.